Treatment of Renal Proteinuria Based on the Theory of “Treat Uncontrolled Discharge by Unblocking” - Wang, Dexin; Ren, Yanyun (Journal of Contemporary Medical Practice, 2025)
Renal proteinuria is frequently associated with dampness and blood stasis. Damp turbidity impairs spleen function, while blood stasis obstructs the renal collaterals, leading to dysfunction of the zang-fu organs and leakage of essential substances. Pathogenic factors accumulate internally, causing stagnation, obstruction of Qi transformation, and failure to separate the clear from the turbid. Consequently, essential substances abnormally permeate into the urine. Specific treatment strategies require careful syndrome differentiation to identify the root cause. Methods such as clearing heat and draining dampness to resolve turbidity, activating blood circulation to resolve stasis, and unblocking collaterals should be employed accordingly. Utilizing the “Treat uncontrolled discharge by unblocking” principle as the therapeutic approach aims to achieve the goal of “securing and reducing proteinuria.” This facilitates the elimination of pathogens, restoration of healthy functioning, and internal retention of essential substances, thereby improving proteinuria.